Electrically switchable polymer stabilised broadband infrared reflectors and their potential as smart windows for energy saving in buildings - Khandelwal, Hitesh; Loonen, Roel C. G. M.; Hensen, Jan L. M.; Debije, Michael G.; Schenning, Albertus P. H. J. (Scientific reports, 2015)
Electrically switchable broadband infrared reflectors that are relatively transparent in the visible region have been fabricated using polymer stabilised cholesteric liquid crystals. The IR reflectors can change their reflection/transmission properties by applying a voltage in response to changes in environmental conditions. Simulations predict that a significant amount of energy can be saved on heating, cooling and lighting of buildings in places such as Madrid by using this switchable IR reflector. We have also fabricated a switchable IR reflector which can also generate electricity. These polymer based switchable IR reflectors are of high potential as windows of automobiles and buildings to control interior temperatures and save energy.